لعام 2020 من منظور رشدي أحمد طعيمة (KSKK) تحليل مادة تعليم اللغة العربية (البلاغة) للصف الثاني عشر بمعاهد المتفوقين التابعة لإدارة التعليم الديني - Habib, Ikhwanul; Muhaiban, Muhaiban; Kurniawan, Vani (Ta'limi | Journal of Arabic Education and Arabic Studies, 2025)
This study aims to analyze the suitability of Arabic teaching materials according to Rusydi Ahmad Thu'aimah's perspective in terms of content or content, organization of material, presentation of material and appearance. in terms of content or content, organization of material, presentation of material and appearance of the book. The method used is descriptive qualitative. The data source used is the Balaghah Arabic Language Book for Grade 12 MAPK Directorate KSKK 2020. Data collection using documents, data analysis techniques using content analysis. The results showed that based on the perspective of Rusydi Ahmad Thu'aimah with the criteria for teaching materials in terms of content or content is in general accordance content is generally appropriate. In terms of organizing the material as a whole is coherent and mutually sustainable. In terms of presenting the material, it pays attention to aspects of language, learning models, and according to standard references. From In terms of the appearance of the book, most of it is appropriate and also follows the printing guidelines of the Ministry of Religious Affairs. However, in the pictures and illustrations section There are images that are not related to the themes discussed. Based on the results of this study, it can be concluded that the book is in accordance with the perspective of Rusydi Ahmad Thu'aimah although there are still things that must be improved such as the presentation of images and illustrations